Ethnological Tourism in the Solomon Islands: An Experience in Applied Anthropology - Michaud, Jean; Maranda, Pierre; Lafrenière, Luc; Coté, Ginette (Anthropologica, 2022)
This paper relates the story of an experiment in tourism in Lau in the Solomon Islands. Whereas tourism is usually seen as a manifestation of globalization, part of a movement toward the eradication of cultural difference, the Lau Cultural Preservation and Tourism Project was conceived to achieve a different goal, the defence of a way of life threatened by Christianity and various economic and political forces. The project involved co-operation between enterprising traditionalists in Lau, an anthropological team based in Quebec and a private travel company. The intent has been to immerse tourists in the traditional culture. Although very few tourists have visited Lau, preparation for tourism has resulted in a revival of traditional ceremonial, the fostering of an entrepreneurial spirit and other changes of a socio-economic and socio-political nature. The authors suggest that such schemes cannot fully succeed if they are dependent on foreign private enterprise.